PENDUGAAN BESARNYA LIMBAH INDUSTRI PERKAYUAN DI KALIMANTAN SELATAN DAN KEMUNGKINAN PEMANFAATANNYA SEBAGAI SUMBER ENERGI - Han Roliadi; Buharman Buharman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The volume of wood waste from sawmills and plywood mills in South Kalimantan was estimated using the regression method. Data were collected from sample mills in the province. Based on the regression analysis, the estimated volume of sawmill waste generated by sawmills in South Kalimantan during the 1981 - 1982 period was 684,353 m3 per year, and that of plywood mill was 221,818 m3 per year. The total wood waste could produced heat energy (fuel) as much as 12.29 x 1011k.cal/year, or 5.42 x 109 KWH per year of electric energy.